Hospital Safety Index analysis in Fars Province hospitals, Iran, 2015-2016 - Peyravi, MD, PhD, Mahmoudreza; Ahmadi Marzaleh, PhD Candidate, Milad; Gandomkar, MSc, Fatemeh; Zamani, PhD Candidate, Aman Allah; Khorram-Manesh, MD, PhD, Amir (American Journal of Disaster Medicine, 2019)
Background and objectives: Hospitals are the vital part of disaster management and their functionality should be maintained and secured. However, it can be the target of natural and man-made disasters. In Iran, Fars Province is prone to major incidents and disasters in its hospitals at any time during the course of a year. This study aimed to examine the Hospital Safety Index (HSI) in all hospitals (public and private) affiliated to Shiraz University of Medical Sciences (SUMS). Materials and methods: This cross-sectional study was conducted during 2015-2016, using the World Health Organization’s HSI checklist. All 58 hospitals in Fars Province affiliated to SUMS were included. The hospital assessment team was formed to collect the data retrospectively and by visiting and interviewing hospital’s authority based on the checklist. The collected data were analyzed using Microsoft Excel. Results: The results showed that in the abovementioned years, the structural safety of hospitals reached the highest optimal level, whereas functional safety reached the lowest level. The results of the studies conducted in 2016 showed that during this year, the overall hospital safety level improved (6 and B). Conclusion: Although safety in hospitals located in Fars Province has improved due to continuous disaster mitigation and preparedness activities, there is still space for more improvement to achieve and maintain higher levels of safety in hospitals. Paying attention to this, the authors recommend that proper policies, legislation, and intra- and inter-institutional coordination are the requirements for a successful outcome.